Polyadenylation of mRNA precursors: mechanism, regulation and connections with other cellular processes - Manley, James (Henry Stewart Talks, 2007)
Polyadenylation of mRNA precursors, The polyadenylation machinery, A surprising complexity in PAP, Hyperphosphorylation by MPF inhibits PAP activity, Gld-2 in cytoplasmic polyadenylation in oocytes, The polyadenylation machinery, CPSF-73 is the 3' processing endonuclease, CPSF-73 is absent in cytoplasmic polyadenylation, CstF protein interactions, Regulation of gene expression by alternative polyadenylation, The C-terminal domain of RNAPII, The CTD can stimulate 3' cleavage in vitro, CPSF links transcription and 3' end formation, RNA15 crosslinks to promoters, Polyadenylation and links to other cellular processes, CstF-50, BRCA1, BARD1, BRCA associated ring domain protein, Why does BARD1 inhibit 3' processing?, DNA damage inhibits 3' processing, How does BARD1 inhibit 3' processing?, BRCA1/BARD1 target RNAPII for ubiquitination, Many factors constitute the mRNA 3' end formation machinery
Reviewed at 2016/01/19